Proceedings of the Singidunum International Tourism Conference - Sitcon 2015 2015
DOI: 10.15308/sitcon-2015-164-167
|View full text |Cite
|
Sign up to set email alerts
|

Bankruptcy Risk Exposure of Serbian Hotels in the Period 2008-2012

Abstract: The purpose of this paper is to determine the indebtedness level of hotels operating in the Republic of Serbia during the period from 2008-2012. It is presumed that the weakened worldwide economy resulted in the decrease of general business solvency and increase of bankruptcy probability in all industries. Service providers have certainly not been left out, and hotels have been in the focus of this paper. We have collected available financial statements of hotels operating in the Republic of Serbia for the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…It has been found that 3-and 5-star hotels are more at risk of bankruptcy than 4-star hotels, while 2-star hotels are at a lower risk. Mizdraković et al (2015) found that there has been deterioration in the financial stability of hotel businesses in 2008-2011 in the Republic of Serbia, while the average value of Altman's Z-score model in 2011 compared to 2008 decreased by about 70%.…”
Section: Literature Reviewmentioning
confidence: 98%
“…It has been found that 3-and 5-star hotels are more at risk of bankruptcy than 4-star hotels, while 2-star hotels are at a lower risk. Mizdraković et al (2015) found that there has been deterioration in the financial stability of hotel businesses in 2008-2011 in the Republic of Serbia, while the average value of Altman's Z-score model in 2011 compared to 2008 decreased by about 70%.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For the purposes of the paper's subject, it is important to point out the possibility of bankruptcy of hotel companies. In order to examine the possibility of bankruptcy in hotel companies from Serbia, Mizdrakoviš et al (2015) applied several models. The business of hotel companies was observed in the period from 2008 to 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kralicek's DF indicator was created on a sample of European companies on the markets in Austria, Germany and Switzerland (Mizdraković et al, 2015). Using the data from financial statements, Professor Kralicek conducted a multivariate discriminatory analysis and formed a business success model which is used for predicting bankruptcy (Zenzerović & Peruško, 2006 After developing this indicator, Professor Kralicek created a QuickTest model that is applied in assessing a company's financial performance and the viability of assets.…”
Section: Models For Identifying Peter Kralicek's Business Successmentioning
confidence: 99%